A Christian bioethical perspective on pre-implantation Genetic Diagnosis (PGD) and Genetic Manipulation (GM) - Kotze, Manitza (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.